2016
DOI: 10.1002/ehf2.12085
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 is down‐regulated in both left atria and left ventricle of ischaemic cardiomyopathy patients and highly related to changes in ventricular function

Abstract: AimsThe kinase ion channel transient receptor potential melastatin 7 (TRPM7) is considered a modulator of cardiac fibrosis progression; nevertheless, we lack of studies analysing its role in human ischaemic cardiomyopathy (ICM). Our objective was to analyse the expression of genes encoding cardiac ion channels in human ICM, focusing on the alterations in mRNA levels of TRPM7 and its relationship with changes in the ventricular function.Methods and resultsRNA‐sequencing was carried out in 13 left ventricular (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…40,54 In ischemic cardiomyopathy, TRPM7 was significantly down regulated in the left atria and ventricle. 39 However, in non-ischemic dilated cardiomyopathy, TRPM7 was shown to be upregulated in patients with ventricular tachycardia. 55 We found a larger magnitude reduction in enhancer eRNA levels compared to reduction in mRNA levels, and this may indicate that additional TRPM7 enhancer regions are active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,54 In ischemic cardiomyopathy, TRPM7 was significantly down regulated in the left atria and ventricle. 39 However, in non-ischemic dilated cardiomyopathy, TRPM7 was shown to be upregulated in patients with ventricular tachycardia. 55 We found a larger magnitude reduction in enhancer eRNA levels compared to reduction in mRNA levels, and this may indicate that additional TRPM7 enhancer regions are active.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6D illustrates alternative enhancer use within the first intron of TRPM7, which encodes the transient receptor potential cation channel subfamily M member, a gene implicated in ischemic cardiomyopathy and cardiac rhythm. 39,40 This intronic enhancer showed significantly lower eRNA expression in heart failure ( Figure 6E), concomitant with a significantly lower expression of TRPM7 in failed hearts ( Figure 6F).…”
Section: Correlation Of Cage-sequencing and Rna-sequencingmentioning
confidence: 95%
“…Up-and downregulation of mRNA levels in TRPM7-dependent malignancies is also typically very modest [44], implicating tight regulation of TRPM7 levels. Consequently, in our study most tetramers of mutant channels can be expected to contain one or more wt TRPM7 proteins which complicates phenotypic characterization.…”
Section: Discussionmentioning
confidence: 99%
“…These ion channels are unique divalent cation channels that are constitutively opened, as well as exhibiting permeability to Mg2+ and Ca2+ . In recent years, increasing displays of evidences have highlighted TRPM6 and TRPM7 channel kinase's as being vital regulators, capable of modulating a variety of physical developments in disease proceedings such as cytoskeleton organization, cell viability, cardiac fibrosis, and magnesium homeostasis . Liu et al reported that Sal B could inhibit mitogen‐activated protein kinase activity.…”
Section: Introductionmentioning
confidence: 99%
“…15 In recent years, increasing displays of evidences have highlighted TRPM6 and TRPM7 channel kinase's as being vital regulators, capable of modulating a variety of physical developments in disease proceedings such as cytoskeleton organization, cell viability, cardiac fibrosis, and magnesium homeostasis. 16,17 Liu et al 18 reported that Sal B could inhibit mitogen-activated protein kinase activity. Prior analysis into Sal B pretreatment has revealed that it largely contributes to the treatment of LPS exposure by improving pulmonary injury and pulmonary microcirculation disturbance.…”
mentioning
confidence: 99%